The Idea of the ANC - Butler, Anthony, 1964- (Book collections on Project MUSE., 2013)
The African National Congress (ANC) is Africa's most famous liberation movement. It has recently celebrated its centenary, a milestone that has prompted partisans to detail a century of unparalleled achievement in the struggle against colonialism and racial discrimination. Critics paint a less flattering portrait of the historical ANC as a communist puppet, a moribund dinosaur, or an elitist political parasite. For such skeptics, the ANC-now in government for two decades-has betrayed South Africans rather than liberating them. South Africans endure deep inequality and unemployment, violent c.